Development and Validation of Gas Chromatography-Mass Spectrometry Method for Determination of Metoprolol in Rabbit Plasma - B. YILMAZ; M. CAVUS (International Journal of Pharma and Bio Sciences, 2010)
This paper describes a gas chromatography-mass spectrometry (GC-MS) method with selected ion monitoring (SIM) for determination of metoprolol in rabbit plasma. Metoprolol and internal standard (IS) atenolol were extracted from plasma and cleaned up by using a single step liquid-liquid extraction. Derivatization was carried out using N-Methyl-N-(trimethylsilyl)trifluoroacetamide (MSTFA). Calibration curves were linear over the concentration range 15-500 ng mL-1. Intra- and inter-day precision values for metoprolol in rabbit plasma were less than 6.4, and accuracy (relative error) was better than 8.8%. The analytical recovery of metoprolol from rabbit plasma averaged out to 91.20%. The limits of detection (LOD) and quantification (LOQ) of metoprolol were 5.0 and 15 ng mL-1, respectively. Also the developed and validated GC-MS method was successfully applied to a pharmacokinetic study of metoprolol in New Zealand white rabbits.